FRI0437 How do we Treat Patients with Focus Score ≥1, but not Consistent with the New American College of Rheumatology Classification Criteria for SjÖGren's Syndrome? Evaluation from Study in Japanese Patients. (10th June 2014) - Ikumi, N.; Inomata, H.; Nagasawa, Y.; Sugiyama, K.; Nozaki, T.; Yokoe, I.; Shiraiwa, H.; Karasawa, H.; Kitamura, N.; Iwata, M.; Matsukawa, Y.; Kobayashi, H.; et al.
Abstract : Background: One of the criteria for Sjögren's syndrome (SS) is focal lymphocytic infiltration in minor salivary gland biopsy (MSGB). Few studies have revealed that the proportion of patients with focus score ≥1 (FS≥1) in SS and even in the dry mouth (DM) group. Objectives: To diagnose SS using the 2012 American College of Rheumatology (ACR) classification criteria for SS, to assess MSGB, and to investigate pathological features, such as FS≥1. Methods: Patients underwent MSGB from September 2009 to November 2013 at one institution. The indications for MSGB included the presence of DM symptoms and serological features. Regardless of connective tissue disease (CTD) before FS evaluation, patients who met the ACR criteria were divided into: Group I, primary SS; Group II, secondary SS; Group III, secondary DM; or Group IV, primary DM (Table). We investigated the correlation between FS≥1 and the diagnosis, and the correlation of the predictor with FS≥1. Statistical analyses were performed using the Fisher's exact or Mann-Whitney tests, Bonferroni multiple comparisons, and multivariate analysis. These analyses were conducted for patients with rheumatoid arthritis (RA) and those with a CTD other than RA. Results: MSGBs were performed on 192 patients (93% female); those with lymphoma, IgG4-related disease, and graft-versus-host disease (7 patients) were excluded. There were 185 patients with SS and DM, including primary SS (82), secondary SS (38), DM with CTDs (22), and DM without CTDs (43). The CTDs included RA (29), systemic lupus erythematosus (15), mixed CTD (3), myositis (6), and systemic sclerosis (8). The classification of the 185 patients by diagnosis and FS≥1 is shown in the Table. More patients in Groups I and II had FS≥1 (P<0.001). Factors such as anti-Ro, anti-La, RF, and IgG correlated with the presence of FS≥1 by univariate analysis, but not by multivariate analysis. The numbers of FS≥1 were significantly different between Groups I and III, I and IV, II and III, and II and IV (all, P<0.05) but not between Groups I and II or Groups III and IV (both, P>0.08). Among the 29 RA patients, 24 had FS≥1, but SS was confirmed in 14 patients only. The numbers of RA patients with FS≥1 in both secondary SS and secondary DM group were not significantly different (P=0.134). However, among patients with CTDs other than RA, the number of patients with FS≥1 in the secondary SS group was significantly different from that in the secondary DM group (P=0.005). Even RA patients with FS≥1 were assigned to DM group. Conclusions: Pathologically, FS≥1 are useful for diagnosing SS. A significant number of patients with FS≥1 was found in both the SS and DM groups. However, patients with noncharacteristic SS may also have RA. Consequently, this study suggests especially the necessity of further investigation and follow-up studies in RA patients who showed inconsistent results with the ACR criteria for DM symptoms. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2684